A Program Evaluation for English Teachers’ Language Competence by Using CIPP Model - Givens Rindu Magnificat Ade Lidiporu; Muchlas Suseno (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
ABSTRACTThe success or failure of a country’s education is greatly affected by the strategic role of teachers and become the reason why teachers’ language ability keeps pace with the times. Due to this issue, it seems that there is no adequate research because the CIPP model of the evaluation program for teaching is still lacking. The study was carried out to evaluate English teachers’ language competence. The model used in this study is the CIPP developed by Daniel L. Stufflebeam, et al. Data collection methods were used are interview, observation, and questionnaire and were analyzed qualitatively. The data validity and reliability were verified by triangulation. The population of this study were the English language teachers at SMP Kabar Baik Cianjur. The result showed the Context, Input, Process and Product of this study. Thus, researcher suggested the school to hold a workshop or training for teachers to increase their language competence.